Programa de aquisição de alimentos (PAA) no estado do Amapá: contribuições e limitações para o fortalecimento da agricultura familiar no município de Mazagão (2010 - 2018) - SANTOS, Geovane Tavares dos (Instituto Federal do Amapá, 2021)
This dissertation analyzed the contributions and limitations of the Food Acquisition Program (PAA) for the strengthening of family farming in the municipality of Mazagão / AP (2010 - 2018). PAA emerged in Brazil in 2003, to meet the pressures of rural social movements that claimed public policies for family farming. Through the Purchase with Simultaneous Donation (CDS) modality, the state of Amapá started its participation in 2009. The city of Mazagão/AP was selected as a place of research by significant and continuous participation in the program's resources. In this way, the guiding question asked was: what were the contributions and limitations of PAA / CDS to the strengthening of family farming in Mazagão municipality from 2010 to 2018? In search of answers, the agrarian question was contextualized from the international and Brazilian theoretical conceptions; It was analyzed the PAA / CDS as a public policy for the strengthening of family farming in Brazil, as well as the contributions and limitations of PAA / CDS in that municipality were identified and discussed. To meet the proposed objectives, was used a quantitative and qualitative reasoned research. The methodological procedures used were exploratory and bibliographic research, documentary research and field research. As field research techniques were Narrative Interview (EN) with representatives of companies and representative of the National Food Company (CONAB), application of the PAA / CDS Satisfaction Assessment Model (MAS) and meetings of focus groups with family farmers (04 groups). The study involved four associated with farmers in the municipality of Mazagão and a total of 18 participants. The results showed that in 10 years of PAA / CDS in the state of Amapá, the state was the 2º in the North Region with the largest participation in the program's resources (R $ 35,116,329.15), of the 16 municipalities, 12 participated. In addition, the municipality with the highest participation was Mazagão / AP, its executed values represent 39% (R $ 12,733,620, 25) of the total state resources. Therefore, this dissertation aims to contribute to the debates on regional development through discussions on peasantry, family farming, agroextractivism, public policies and mainly about the PAA / CDS in the Amazon, Amapá and Mazagão.